Ethyl 1-(2-hydroxyethyl)-2-phenyl-1H-benzimidazole-5-carboxylate - Hamzah, Nurasyikin; Abd Hamid, Shafida; Abdul Rahim, Aisyah Saad; Rosli, Mohd Mustaqim; Fun, Hoong-Kun (International Union of Crystallography, 2010)

(untitled)
There are two molecules in the asymmetric unit of the title compound, C18H18N2O3. In each one, the benzimidazole ring system is essentially planar, with maximum deviations of There are two molecules in the asymmetric unit of the title compound, C18H18N2O3. In each one, the benzimidazole ring system is essentially planar, with maximum deviations of 0.027 (1) and 0.032 (1)Å, and makes dihedral angles of 38.64 (6) and 41.48 (6)°, respectively, with the attached benzene rings. An intramolecular C—HO hydrogen bond is observed in each molecule. The two independent molecules are connected into a dimer by two intermolecular O—HN hydrogen bonds. In the crystal, molecules form a two-dimensional layers parallel to (012) via weak intermolecular C—HO hydrogen bonds. In addition, weak π-π stacking interactions are observed with centroid–centroid distances of 3.5244 (12) and 3.6189 (12) Å.